Potential Effects of Pomegranate Polyphenols in Cancer Prevention and Therapy. (9th June 2015) - Turrini, Eleonora; Ferruzzi, Lorenzo; Fimognari, Carmela
Abstract : Cancer is the second leading cause of death and is becoming the leading one in old age. Vegetable and fruit consumption is inversely associated with cancer incidence and mortality. Currently, interest in a number of fruits high in polyphenols has been raised due to their reported chemopreventive and/or chemotherapeutic potential. Pomegranate has been shown to exert anticancer activity, which is generally attributed to its high content of polyphenols. This review provides a comprehensive analysis of known targets and mechanisms along with a critical evaluation of pomegranate polyphenols as future anticancer agents. Pomegranate evokes antiproliferative, anti-invasive, and antimetastatic effects, induces apoptosis through the modulation of Bcl-2 proteins, upregulates p21 and p27, and downregulates cyclin-cdk network. Furthermore, pomegranate blocks the activation of inflammatory pathways including, but not limited to, the NF- κ B pathway. The strongest evidence for its anticancer activity comes from studies on prostate cancer. Accordingly, some exploratory clinical studies investigating pomegranate found a trend of efficacy in increasing prostate-specific antigen doubling time in patients with prostate cancer. However, the genotoxicity reported for pomegranate raised certain concerns over its safety and an accurate assessment of the risk/benefit should be performed before suggesting the use of pomegranate or its polyphenols for cancer-related therapeutic purposes.